Peran Berpikir Kreatif dalam Proses Pembelajaran Matematika - Supardi U.S. (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2012)
This study aimed to investigate the influence of creative thinking on the subject of mathematics learning achievement. The benefit of this study is to provide information of what the impact of creative thinking on mathematics learning achievement. The method used in this study is a survey method correlation with regression analysis. The population is class IX SMP At-Taqwa. Samples were 30 taken by purposive sampling technique. Instruments to collect data on the study of creativity in the form of a test that consists of 7 items and instruments question multiple-choice test consisting of 20 items about. From the alculations, the magnitude of the correlation coefficient or rhitung was 0.37 and the 5% significance level of 0.361 it can be seen that the price rhitung> rtabel means there is a significant correlation between creative thinking mathematics learning achievement. From the calculation of the level test hypotheses derived Fhitung = 4.45 by looking at the tables on the distribution F with the real level of 5% or ? = 5% was obtained Ftable = 4.20 in order to obtain that Fhitung ? F table. This concluded that there are positive effects of creative thinking mathematics learning achievement.